2023
DOI: 10.1101/2023.09.26.559572
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent generation of atypical prions in knock-in mouse models of genetic prion disease

Surabhi Mehra,
Matthew E.C. Bourkas,
Lech Kaczmarczyk
et al.

Abstract: Most cases of human prion disease arise due to spontaneous misfolding of wild-type or mutant prion protein. Though recapitulating spontaneous prion conversion in animal models has proven challenging, transgenic mice expressing the misfolding-prone bank vole prion protein (BVPrP) recreate certain key aspects of sporadic and genetic prion disease. However, it remains unclear whether spontaneous prion generation can occur in the absence of protein over-expression and how disease-causing mutations affect prion str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…For this study, we used recently developed knock-in mouse models of inherited prion diseases with shortened lifespans (26) We also included PSCMA, an oral, brain-penetrant compound previously shown to inhibit PrP Cdependent Aβ oligomer toxicity in vivo (35) because we found that it could inhibit spontaneous D177N Mo PrP Sc propagation in sPMCA reactions (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, we used recently developed knock-in mouse models of inherited prion diseases with shortened lifespans (26) We also included PSCMA, an oral, brain-penetrant compound previously shown to inhibit PrP Cdependent Aβ oligomer toxicity in vivo (35) because we found that it could inhibit spontaneous D177N Mo PrP Sc propagation in sPMCA reactions (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The methods used to design and produce kiBVI D178N and kiBVI E200K mice were originally described in a complementary manuscript (26). Briefly, gene targeting in V6.…”
Section: Mouse Modelsmentioning
confidence: 99%
“…The methods used to design and produce kiBVI D178N and kiBVI E200K mice are described in a complementary manuscript [ 26 ]. Briefly, gene targeting in V6.5 embryonic stem cells was performed at the DZNE/Bonn University using CRISPR technology as described previously [ 27 ].…”
Section: Methodsmentioning
confidence: 99%